1995
DOI: 10.1530/eje.0.1320699
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of central precocious puberty with depot leuprorelin

Abstract: We evaluated the pituitary and gonadal suppression in 40 girls and nine boys treated with depot leuprorelin (3.75 mg sc if body weight > or = 20 kg, 1.87 mg if body weight < 20 kg) every 28 days for central precocious puberty. Gonadal suppression was obtained in most of the children with this dose: 3 months after initiation of the treatment, 85% of children had a peak plasma luteinizing hormone response to gonadotropin-releasing hormone < 3 IU/l and the gonadal axis remained suppressed throughout the duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
9

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 12 publications
5
51
0
9
Order By: Relevance
“…The hormonal monitoring in our patient showed constant pituitary-gonadal suppression of a comparable degree as seen in patients treated with the 1-month leuprorelin depot [4, 5]or other GnRH agonists such as triptorelin [19]. The return to normal size for age of the uterus and ovaries was also comparable to treatment with 1-month depots of various GnRH agonists [4].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The hormonal monitoring in our patient showed constant pituitary-gonadal suppression of a comparable degree as seen in patients treated with the 1-month leuprorelin depot [4, 5]or other GnRH agonists such as triptorelin [19]. The return to normal size for age of the uterus and ovaries was also comparable to treatment with 1-month depots of various GnRH agonists [4].…”
Section: Discussionsupporting
confidence: 70%
“…In a randomized study, patients with CPP treated with depot triptorelin attained a mean final height above their mean target height, whereas patients treated with short-acting buserelin did not [3]. One-month depot preparations are available for the GnRH agonists leuprorelin [4, 5], triptorelin [6]and goserelin [7]. All have been shown to be effective in suppressing the pituitary-gonadal axis.…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous intolerance to depot GnRH agonists has been reported and is mostly due to reaction to the lactide-coglycolide polymer (9,11,16,26,27). In the present study, mild-to-moderate local reactions at the injection site were reported in 8% of the children, and injection pain in only 3%.…”
Section: Discussionsupporting
confidence: 39%
“…Triptorelin (Decapeptyl® Depot) ve Leuprolid (Lucrin Depot®) asetat tedavide kullanılan başlıca GnRH analoglarıdır. Önerilen doz Leuprolid asetat için 150-300 mcg/kg/ay (3.75-7.5 mg/ay), Triptorelin için ise 100-150 mcg/kg/aydır (3,4,5).…”
Section: Discussionunclassified